HISTOPATHOLOGY OF RAT KIDNEY EXPOSED TO LEAD HEAVY METAL - Dominika, Kevin; Berata, I Ketut; Setiasih, Ni Luh Eka (Buletin Veteriner Udayana, 2022)
Lead is a non-essential heavy metal which is toxic to kidney, carcinogenic, and teratogenic if get inside animal or even human’s body. The research aims to determine the histopatologic view of rat’s kidney which was exposed to lead with different doses. The research uses 20 of 2 months old Wistar strain white rat with 250-300 g body weight. The research uses completely randomized design  with 4 treatments, which is control (P0), 0.5 ppm lead acetate (P1), 1.0 ppm lead acetate (P2), and 2.0 lead acetate (P3). Treatment were given daily for 30 days and on day 31 euthanation and necropsy was performed then the kidney tissue was removed and put into 10% neutral buffer formalin. Then histopathologic preparation with hematoxilyn eosin stain was made. Kidney histopathology changes that were examined were bleeding, necrosis, and inflammation. Severity of the lesion was made into scoring wiith mild category of it was focal, moderate if it was multifocal, and severy if it was diffuse. The Kruskal-Wallis test of the histopathologic examination result of rat’s kidney which was exposed to lead acetate shows a significant bleeding, necrosis and even nephritis (inflammation) lesion compared to without the exposure to lead acetate (control). The Mann-Whitney test shows a significant result which varies between bleeding, necrosis, even nephritis (inflammation) lesion. with a It can be concluded that the administration of lead acetate with the dose of 0.5 ppm, 1.0 ppm, even 2.0 ppm can cause bleeding, necrosis even nephritis compared to control and the administration of 2.0 ppm dose shows the most severe lesions.  There needs to be a continued research regarding the effects of lead with higher doses.